The height premium in Indonesia - Sohn, Kitae (2015)
© 2014 Elsevier B.V. All rights reserved.Analyzing the Indonesian Family Life Survey for the year 2007, this paper estimates that a 10 cm increase in physical stature is associated with an increase in earnings of 7.5% for men and 13.0% for women, even after controlling for an extensive set of productivity variables. When the height premium is estimated by sector, it is 12.3% for self-employed men and 18.0% for self-employed women; a height premium of 11.1% is also estimated for women in the private sector. In the public sector, however, the height premium estimate is not statistically significant for either men or women. This paper provides further evidence of discrimination based on customers' preferences for tall workers.